Peptide from sea anemone metridium senile affects transient receptor potential ankyrin-repeat 1 (TRPA1) function and produces analgesic effect - Logashina, Yulia A.; Mosharova, Irina V.; Korolkova, Yulia V.; Shelukhina, Irina V; Dyachenko, Igor A.; Palikov, Victor A.; Palikova, Yulia A.; Murashev, Arkadii N.; Kozlov, Sergey A.; Stensvåg, Klara; Andreev, Yaroslav A. (Journal of Biological Chemistry, 2017)
Source at: http://doi.org/10.1074/jbc.M116.757369 The Transient Receptor Potential Ankyrin-repeat 1 (TRPA1) is an important player in pain and inflammatory pathways. It is a promising target for novel drugs development for treatment of a number of pathological states. A novel peptide producing significant potentiating effect (up to ~90%) on AITC- and diclofenac-induced currents of TRPA1 was isolated from the venom of sea anemone Metridium senile . It is 35 amino acid peptide cross-linked by two disulfide bridges, named τ-AnmTX Ms 9a-1 (short name Ms 9a-1) according to structure similarity to other sea anemone peptides belonging to structural group 9a. The structure of two genes encoding different precursor proteins of Ms 9a-1 were determined. Peptide Ms 9a-1 acted as a positive modulator of TRPA1 in vitro but did not cause pain or thermal hyperalgesia when injected in mice hind paw. Intravenous injection of Ms 9a-1 (0.3 mg/kg) produced significant decrease of nociceptive and inflammatory response to AITC (agonist of TRPA1) and reversed CFA-induced inflammation and thermal hyperalgesia. Taken together, these data support the hypothesis that Ms 9a-1 potentiates response of TRPA1 to endogenous agonists followed by persistent functional loss of TRPA1-expressing neurons. We can conclude that TRPA1 potentiating may be useful as therapeutic approach since Ms 9a-1 produce significant analgesic and anti- inflammatory effect in mice models of pain.